Acesso à justiça e voluntariado: livre exercício pelos advogados públicos federais como instrumento de efetivação da garantia constitucional - Vieira, Andréa Maria dos Santos Santana (2013)
The Constitution insures the right to access justice as a kind of citizenship realization. How to the man isn’t allow do justice with your own hands, exepting in special cases under the law that configures the justice access among the most individual basic rights. Although it builds a basic social right aiming insures to implement the other rights, several are the obstacles to concretize it, starting with the dificulty to access the justice assistence. The first step to the full justice access consists at an advocacy service. So, the materialization of an assistence model would be by increasing the Public Defensor Office structure, it is verified that the oficial model provided by the State doesn’t reach people’s needs. From the dificulties of the lower social economic class to realizing of their rights, the present study seek to show the needing to amplify the ways to access further the State’s tutelage. As a presente reality, the promises of an access still not efective in practice that shows that State doesn’t answer the whole compliance of the constitucional guarantee. By a phenomenological approach the research aims to show that the exercise of free volunteering by Federal Government Attorney’s aims to contribute to the realization of the constitutional guarantee of access to justice. For this, first will be present the economic barriers to effective justice access, the precariousness of the system and the needs for inclusion of new benchmarks of participation, followed by the social commitment of advocacy to implement the legal system access. Also shown are the legal obstacles imposed by the state in an attempt to dispel the legitimacy of Attorneys Federal Government to exempt voluntary practice restriction. Finally, it will seek to establish, based on constitutional law, the need to overcome the obstacles to effective justice access.